The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1093/humrep/der444
|View full text |Cite
|
Sign up to set email alerts
|

Robotic treatment of colorectal endometriosis: technique, feasibility and short-term results

Abstract: To our knowledge, this is the first study reporting the feasibility and short-term results and complications of laparoscopic robotic-assisted treatment of DIE with colorectal involvement. We demonstrate that this approach is feasible and safe, without conversion to laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 21 publications
(23 reference statements)
3
44
0
4
Order By: Relevance
“…A 14-month study of 22 patients with this disease showed significant symptom improvement postoperatively, and no cases of laparoscopic conversion [23].…”
Section: Discussionmentioning
confidence: 93%
“…A 14-month study of 22 patients with this disease showed significant symptom improvement postoperatively, and no cases of laparoscopic conversion [23].…”
Section: Discussionmentioning
confidence: 93%
“…Ercoli est l'un des rares à avoir comparé ces deux mé thodes en laparoscopie robot-assisté e [10]. Vingt-deux femmes atteintes d'endomé triose avec localisation colorectale ont é té opé ré es.…”
Section: Discussionunclassified
“…attribué s au fait que les femmes aient une atteinte plus sé vè re dans le groupe ré section. En chirurgie robotique, comme en laparoscopie conventionnelle, la duré e d'intervention est significativement plus longue en cas de ré section digestive par rapport au shaving [8,10]. Par ailleurs, la laparoscopie robot-assisté e augmente la duré e opé ratoire par rapport à la laparoscopie conventionnelle.…”
Section: Tableauunclassified
See 1 more Smart Citation
“…5860 The three-dimensional view offers excellent visualization, which may be most beneficial in identifying suspected implants. However, the robotic platform has the distinct disadvantage of offering only a unidirectional view within the abdominal cavity.…”
Section: Robot Assistancementioning
confidence: 99%